Problematika Pendidikan Islam Kontemporer - Syafrin, Nirwan (Ta'dibuna: Jurnal Pendidikan Islam, 2018)
The crisis inciting Muslims today is acute und multifaceted. There has been various and serious endeavors taken by numerous Muslim groups: activists, educationists, and intellectuals. However, such an effort has yet produced any significant result. Many Muslim intelligentsias seem to have unanimously agreed that the nature of the present crisis is that of intellectualism or thought. There is no doubt that thought is produced through education. The crisis of thought is therefore tantamount to the crisis of education. What is the problem of our education? Apart from being influenced by liberalism and secularism, it lost its spirit (ruh). It becomes worldly oriented, focusing merely on attaining material pleasure.